Spatial visualization provides insight into immune modulation by an L-DBF vaccine formulation against Shigella - Lu, Ti; Kramer, Skyler T.; York, Mary A.; Zahan, Mst Nusrat; Howlader, Debaki R.; Dietz, Zackary K.; Whittier, Sean K.; Bivens, Nathan J.; Jurkevich, Alexander; Coghill, Lyndon M.; Picking, William D.; Picking, Wendy L. (Frontiers in Immunology, 2025)
Shigellosis remains a global public health problem, especially in regions with poor sanitation measures. Our prior work has demonstrated the protective efficacy of a three-dose regimen of L-DBF, a recombinant fusion of IpaD and IpaB from Shigella flexneri with the LTA1 moiety of enterotoxigenic E. coli labile toxin. Here, we investigate how a two-dose regimen (one prime and one booster) of L-DBF, formulated in an oil-in-water emulsion called ME, modulates immune responses in the lung using a spatial transcriptomics approach. Our findings show significant changes in the lung immune landscape following the vaccination, including increased expression of B cell markers, antigen presentation genes, and T cell-associated markers. Our analysis also revealed significant reprogramming of fibroblasts and cardiomyocytes, showing that fibroblasts are shifted from extracellular matrix production to immune modulation, while cardiomyocytes enhanced the signaling for immune cell recruitment and vascular stability. The communication between alveolar type 2 (AT2) cells and cardiomyocytes also increased, reflecting coordinated support for immune readiness and maintaining tissue integrity. These findings underscore the potential of L-DBF/ME vaccination to enhance both humoral and cellular immunity, as well as to reshape lung immune architecture while enhancing immune readiness, thereby offering a promising approach for effective protection against Shigella infections.